Combined multi-channel intraluminal impedance measurement and pHmetry in the detection of gastroesophageal reflux disease in children with cystic fibrosis - Emília da Silva Gonçalves; José Dirceu Ribeiro; Fernando Augusto Lima Marson; Ciro Garcia Montes; Antônio Fernando Ribeiro; Jochen Georg Mainz; Adyléia Aparecida Dalbo Contrera Toro; Juliana Helena Zamariola; Daniela Souza Paiva Borgli; Elizete Aparecida Lomazi; Maria de Fátima Corrêa Pimenta Servidoni (Elsevier, 2023)
Objective: To assess the prevalence of GERD exclusively by means of multichannel intraluminal impedanciometry associated with pH monitoring (MIIpH) and compare it with respiratory symptoms in children with CF. To compare MIIpH with pHmetry alone to perform GERD diagnosis. Methods: An analytical cross-sectional study was conducted with children diagnosed with CF who underwent MIIpH. Clinical and laboratory markers, including respiratory and digestive symptoms, were used for comparative analyses. High-resolution chest computed tomography was performed on patients with symptoms of chronic lung disease. Severity was classified according to the Bhalla score. Results: A total of 29 children < 10 yo (18 girls) were evaluated; 19 of whom with physiological GER and 10 with GERD. Of the children with GERD, seven had predominantly acid GER, two acid+non-acid GER, and one non-acid GER. Three patients had GERD diagnosed only by MIIpH. Bhalla scores ranged from seven to 17.75 with no significant relationship with GERD. The number of pulmonary exacerbations was associated with a decrease in esophageal clearance regardless of the position in pHmetry and MIIpH. Conclusions: The prevalence of GERD was 34% in children with CF. There was no association between respiratory disease severity and GER types. MIIpH detected 30% more patients with GERD than pHmetry.